Draft Annual Plan 2006-07 West Bengal - Planning Commission (Planning Commission, 2006)
There have been remarkable achievements in the production of foodgrains in the State of West Bengal in recent years. This has been the result of progressive and systematic planning and implementation of various crop development programmes/schemes (State Plan, Central Sector and Centrally Sponsored Schemes) launched by the State Govt., the dedication of our people engaged in agriculture, involvement of “Panchayati Raj System” and application of modem crop production technology in the field. The average production of foodgrains during Ninth Plan period was 147.78 lakh tonnes. During the year 2003-2004 the State achieved total foodgrains production of 159.55 lakh tonnes compared to 155.22 lakh ton during 2002-03, in spite of erratic monsoon and unfavourable weather condition in mid to late October.
Development and Planning Department Government of West Bengal